Decision-making by children - Shelly Lundberg; Jennifer Romich; Kwok P. Tsang (Institute for the Study of Labor (IZA), 2007)
In this paper, we examine the determinants of decision-making power by children and young adolescents. Moving beyond previous economic models that treat children as goods consumed by adults rather than agents, we develop a noncooperative model of parental control of child behavior and child resistance. Using child reports of decision-making and psychological and cognitive measures from the NLSY79 Child Supplement, we examine the determinants of shared and sole decision-making in seven domains of child activity. We find that the determinants of sole decision-making by the child and shared decision-making with parents are quite distinct: sharing decisions appears to be a form of parental investment in child development rather than a simple stage in the transfer of authority. In addition, we find that indicators of child capability and preferences affect reports of decision-making authority in ways that suggest child demand for autonomy as well as parental discretion in determining these outcomes.
Keywords: 330; Kinder; Entscheidung; Verantwortung; Familienökonomik; Gruppenentscheidung; USA